Pengaruh Pendampingan Dan Motivasi Aparatur Desa Terhadap Efektifitas Pelaksanaan Program Pemberdayaan Masyarakat Fakir Miskin Di Desa Sei Mencirim Kecamatan Kutalimbaru Kabupaten Deli Serdang - Artha Lumbantobing (Jurnal Ilmu Sosial Dan Politik, 2022)
This study aims to answer the achievements of the implementation of the empowerment program for the poor in Sei Mencharim Village, Kutalimbaru District, Deli Serdang Regency. With a quantitative approach, the population of all village government officials and underprivileged communities is 414 families, with a sample of 70 families. Data analysis used linear regression analysis. The results show that the Assistance and Motivation of Village Apparatuses together has a positive and significant effect on the empowerment of the Poor Pakir community. It can be seen from f count 9.308 > from f table 0.008. and significant value obtained 0.000 <0.05 (5%). That is, in this study, mentoring and motivation jointly affect the empowerment of the poor in Sei Village, which characterizes Kutalimbaru Deli Serdang. With the influence of mentoring and motivation of village officials on empowering the poor, it is better if the Sei Mencharacter Village Apparatus, Kutalimbaru District, Deli Serdang Regency is more effective in empowering the community through mentoring and motivating towards a prosperous society.